CREG1 restricts ALV-J replication via the mitochondrial dysfunction–driven activation of innate immunity and apoptosis - Zhang, Qihong; Wang, Meihuizi; Pan, Ming; Xia, Junliang; Xu, Tao; Luo, Wen; Zhang, Xiquan (Frontiers in Immunology, 2026)
BackgroundHost antiviral defense relies on key regulatory genes that coordinate immune signaling and cellular homeostasis, yet their roles in J subgroup avian leukosis virus (ALV-J) infection remain poorly defined. Here, we identify cellular repressor of E1A-stimulated genes 1 (CREG1) as a key regulator of mitochondrial function and a critical immune-related gene involved in ALV-J infection. The objective of this study was to explore the effects and underlying mechanisms of CREG1 in the context of ALV-J infection.MethodsIn this study, transcriptomic analysis and RT-qPCR revealed that the expression of CREG1 is significantly upregulated in the spleen tissues of ALV-J infected chickens. By overexpressing and silencing CREG1 in cultured cells, and using Western blotting, transmission electron microscopy, immunofluorescence, and flow cytometry, we comprehensively validated its effects on viral replication, mitochondrial function, and apoptosis.ResultsOverexpression of CREG1 upregulates the expression of I-IFN and certain interferon-stimulated genes (ISGs), thereby suppressing viral replication. Mechanistically, overexpression of CREG1 induces mitochondrial dysfunction, characterized by a decrease in mitochondrial membrane potential (Δψm), reduced adenosine triphosphate (ATP) production and respiratory chain activity, enhanced mitophagy, and increased release of mitochondrial DNA (mtDNA), which in turn triggers the activation of innate immune responses. Mitochondrial dysfunction further leads to the cytosolic release of cytochrome c and an increase in reactive oxygen species (ROS) levels, thereby triggering a robust apoptotic response. Moreover, the regulation of mitochondrial function by CREG1 depends on its interaction with the mitochondrial chaperone protein heat shock protein 1 (HSPD1), and their co-expression synergistically amplifies the antiviral response.ConclusionsOverall, we identify CREG1 as a potent antiviral gene and underscore the pivotal roles of mitochondria-mediated innate immunity and apoptosis during ALV-J infection.